THE ROLE OF THE RHYTHMIC AND SYNTACTICAL VARIATIONS IN REALIZATION OF TRIOLET SYNERGETIC POTENTIAL - E. V. Bublik (Гуманитарные и юридические исследования)
The article treats triolet as a synergetic system. The synergetic potential of lexical, syntactic and rhythmic variations in the composition of triolet is considered in poetry of Igor Severyanin.